Kajian Bibliometrik terhadap Publikasi Ilmiah tentang Septoplasty: Visualisasi Tren dan Topik Populer - Christanto, Antonius (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze trends and popular topics in scientific publications on septoplasty using bibliometric methods. Bibliometric analysis is used to measure and map scientific publication data, including the number of publications, authors, institutions, and frequently occurring keywords. The data were collected from international scientific databases and then analyzed using visualization techniques such as keyword mapping, author collaboration networks, and citation analysis. The results show that the number of publications on septoplasty has increased significantly in recent years, with main focuses on surgical techniques, clinical outcomes, and complications. Furthermore, this study identifies the most productive authors and institutions as well as patterns of international collaboration. These findings provide a comprehensive overview of the development of septoplasty research and serve as an important reference for future studies.